2D Metal–Organic Framework Derived CuCo Alloy Nanoparticles Encapsulated by Nitrogen‐Doped Carbonaceous Nanoleaves for Efficient Bifunctional Oxygen Electrocatalyst and Zinc–Air Batteries. Issue 55 (5th September 2019) - Huo, Meiling; Wang, Bin; Zhang, Chaochao; Ding, Shuping; Yuan, Haitao; Liang, Zuozhong; Qi, Jing; Chen, Mingxing; Xu, Yang; Zhang, Wei; Zheng, Haoquan; Cao, Rui
Abstract: The development of efficient bifunctional electrocatalysts for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) still remains a challenge in a wide range of renewable energy technologies. Herein, CuCo alloy nanoparticles encapsulated by nitrogen‐doped carbonaceous nanoleaves (CuCo‐NC) have been synthesized from a Cu(OH)2 /2D leaf‐like zeolitic imidazolate framework (ZIF‐L)‐pyrolysis approach. Leaf‐like Cu(OH)2 is first prepared by the ultrasound‐induced self‐assembly of Cu(OH)2 nanowires. The efficient encapsulation of Cu(OH)2 in ZIF‐L is obtained owing to the morphology fitting between the leaf‐like Cu(OH)2 and ZIF‐L. CuCo‐NC catalysts present superior electrocatalytic activity and stability toward ORR and OER over the commercial Pt/C and IrO2, respectively, which are further used as bifunctional oxygen electrocatalysts in Zn–air batteries and exhibit impressive performance, with a high peak power density of 303.7 mW cm −2, large specific capacity of up to 751.4 mAh g −1 at 20 mA cm −2, and a superior recharge stability. Abstract : A leaf on the wind : CuCo alloy nanoparticles encapsulated by nitrogen‐doped carbonaceous nanoleaves (CuCo‐NC) have been synthesized by a Cu(OH)2 /2D leaf‐like zeolitic imidazolate framework pyrolysis approach. CuCo‐NC presents superior electrocatalytic activity and stability toward the O2 reductions and evolution reactions, and could be used as a bifunctional oxygen electrocatalyst in Zn–air batteries (see figure).